JENIS-JENIS TINDAK KOMISIF DARI UNGKAPAN-UNGKAPAN DI FILM "SENIOR YEAR" - Fanny Virginia; Ambalegin Ambalegin (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2022)
Movie becomes one of the increasingly popular media that has pragmatics phenomena. The existence of the phenomena is influenced by the involvement of speaker, interlocutor, and context as pragmatics elements. Through a pragmatic perspective, this descriptive qualitative research revealed the types of commissive acts in movie. This research took a 2022 movie entitled “Senior Year” as the data source. Data were all collected from commissive acts utterances uttered by all characters in the movie. The researcher collected data by implementing observational method with non-participatory technique. For the data analysis, the researcher analyzed by taking pragmatic identity method and pragmatic competence- in equalizing technique. Commissive acts theory discovered Searle and Vanderveken was used as the main theory to analyze data. As a result, this research confirmed that five commissive acts types were realized by the movie characters and there had 62 commissive utterances in total. 17 data were identified as accept, threaten and promise had nine data for each type, 16 data were found in offer, and refuse got 11 data. Dominant type belonged to accept as the characters frequently committed themselves to accept the offer of future action from other characters.